The Impact of Allowances and Infrastructure on Disaster Management Agency Performance in Bontang - Sunaryo, Sunaryo; Daryono, Daryono; Indarto, Kus (Journal of Transformative Governance and Social Justice, 2026)
This study seeks to ascertain how the performance of the Bontang City Regional Disaster Management Agency is impacted by the provision of allowances and the fulfillment of facilities and infrastructure. Data collection strategies used by the researchers included direct observation, questionnaires or surveys, in-depth interviews, and documentation. The study's findings suggest that giving allowances and meeting infrastructure and facilities needs have an impact on employee performance and have a simultaneously positive and significant impact on employee performance. The more the allowances are received and the facilities and infrastructure are fulfilled, the more motivated the workers at BPBD Bontang are, which leads to higher performance levels. To improve the performance of BPBD Bontang employees, allowances should be added so that employees feel secure and more enthusiastic about their work. Adequate facilities and infrastructure should also be provided to facilitate employee performance, thereby improving the performance of BPBD Bontang employees. To add employee allowances, it is necessary to analyse the workload and propose an increase in allowances, as well as provide clear reasons for proposing the increase in allowances.